DAMPAK PAJANAN KEBISINGAN MESIN EXTRUDER TERHADAP GANGGUAN KOMUNIKASI PADA PEKERJA DI PT. X SIDOARJO - Aufrieda Ariestyajuni (UNUSA Press, 2019)
Exposure to extruder machine noise can cause non-auditory effects such as communication disorders. The purpose of this study was to analyze the effect of extruder machine noise exposure on the non-auditory effects of PT. X Sidoarjo in 2018. This research is an observational analytic study with cross sectional design. The research respondents were 60 people consisting of two groups, namely groups of workers in the extruder unit and office staff groups. The group of workers in the extruder unit is a group that is exposed to high noise while the office staff group is a control group that is exposed to low noise. Sampling is done by simple random sampling method. The independent variables in this study were the level of extruder machine noise exposure and the dependent variable in this study, which were non auditory effects which included communication disorders. Noise in the area of the extruder machine shows a number that exceeds the Threshold Value The limit is 85 dBA. The results of the questionnaire analysis showed that 81.6% of workers felt a communication disruption due to exposure to extruder machines at PT. X Sidoarjo. Efforts can be made to reduce the level of extruder noise exposure by the need for periodic engine maintenance, dampers to reduce the noise level of the extruder machine and work rotation is needed to reduce the impact of extruder machine noise exposure on workers.